2020
DOI: 10.1111/1365-2745.13537
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on the demography of a perennial plant depend on interactions with size and environment

Abstract: Age‐dependence of the demographic rates survival, fecundity and individual growth is a fundamental aspect of population biological theory. Knowledge about plant ageing can also be important for conservation and agriculture as it will improve the accuracy of population viability assessments and long‐term performance assessments in perennial crops. Recent studies show age effects on demographic rates for several plant species, yet much remains to be learned about the patterns and mechanisms of plant ageing, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
1
14
1
Order By: Relevance
“…For example, perennials (e.g. clumping perennial grasses) may vary in productivity due to life span, energy allocation to growth/reproduction and/or to how much biomass accumulates from year to year (Baden et al, 2021; Lundgren & Des Marais, 2020; Mooney et al, 1986), resulting in changes in overall productivity and diversity. Although we did not have enough data to examine time lags, considering lagged effects of precipitation and soil moisture and temporal autocorrelation between years on the plant and herbivore communities community is an important way forward (Sala et al, 2012; Zhu et al, 2014), as is exploring how life histories of plants and herbivores may play into the responses of these communities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, perennials (e.g. clumping perennial grasses) may vary in productivity due to life span, energy allocation to growth/reproduction and/or to how much biomass accumulates from year to year (Baden et al, 2021; Lundgren & Des Marais, 2020; Mooney et al, 1986), resulting in changes in overall productivity and diversity. Although we did not have enough data to examine time lags, considering lagged effects of precipitation and soil moisture and temporal autocorrelation between years on the plant and herbivore communities community is an important way forward (Sala et al, 2012; Zhu et al, 2014), as is exploring how life histories of plants and herbivores may play into the responses of these communities.…”
Section: Discussionmentioning
confidence: 99%
“…Local population dynamics and dispersal are the main mechanistic drivers for spatial population spread (Hastings et al., 2005 ; Kot et al., 1996 ; Schreiber & Beckman, 2020 ; Skellam, 1951 ). As remnant habitats become smaller and more fragmented, considerable variation in local population dynamics and seed dispersal may occur among remnant patches, due to environmental heterogeneity and context dependency of local population dynamics and seed dispersal (Baden et al., 2021 ; Clobert et al., 2012 ). Accordingly, recent studies emphasize the significance of intraspecific variation in seed dispersal (Chen & Giladi, 2020 ; Snell et al., 2019 ) and local population dynamics (Yang et al., 2021 ) for predicting how plants respond to environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence has shown various survivorship curves (Harper, 1967), and the chance to survive may even rise with age (Baudisch et al., 2013; Lauenroth & Adler, 2008). More recent studies have shown that age may positively and negatively influence the vital rates, that is, survival, growth and fecundity, of plant individuals in herbaceous species (Baden et al., 2021; Baudisch et al., 2013; Roach, 2012). Moreover, plant age has been shown to significantly control biomass allocation in plants, and may thereby affect competitive interactions (Doležal et al., 2020).…”
Section: Introductionmentioning
confidence: 99%